PERANAN BENTIK MAKRO INVERTEBRATA DALAM MENILAI KUALITAS SUNGAI CISADANE - Sri Unon Purwati (Jurnal Ecolab, 2007)
Cisadane River is a big river crossing the province of west java and banten. because of the increasing human activities surrounding the cisadane river indicating the water quality was decreasing year by year, Decresing of water quality can be monitored through water discharge., physical and chemical properties. the study were conducted twice a yea, on june and august from 2003 to 2006 at 14 monitoring stations. Parameters analyzed were pH, DO, BOD, COD, NO2, NO3, NH3, Phenol, and Heavy metals. the results indicating that the bentic macroinvertebrate was affected by DO, BOD, and COD. It were indicating the chemical and biological aspect are important for integrated asessment of water quality. The bentic macroinvertebrate is a bottom organism which make balance aquatic system, so it can be used as an water quality indicator.